2003
DOI: 10.1136/bmj.326.7404.1427
|View full text |Cite
|
Sign up to set email alerts
|

Value of low dose combination treatment with blood pressure lowering drugs: analysis of 354 randomised trials

Abstract: Objective To determine the average reduction in blood pressure, prevalence of adverse effects, and reduction in risk of stroke and ischaemic heart disease events produced by the five main categories of blood pressure lowering drugs according to dose, singly and in combination. Design Meta-analysis of 354 randomised double blind placebo controlled trials of thiazides, blockers, angiotensin converting enzyme (ACE) inhibitors, angiotensin II receptor antagonists, and calcium channel blockers in fixed dose. Subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

29
804
5
44

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 1,034 publications
(906 citation statements)
references
References 33 publications
29
804
5
44
Order By: Relevance
“…The results are also consistent with previous studies of combination therapy consisting of a CCB and an ARB 28, 29, 30, 31. Importantly, a greater and earlier effect on BP control via combination therapy has the potential to provide greater CV benefit, as suggested by meta‐analysis2 and by review of major clinical trials with CCB/RAS blocker therapies 32…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…The results are also consistent with previous studies of combination therapy consisting of a CCB and an ARB 28, 29, 30, 31. Importantly, a greater and earlier effect on BP control via combination therapy has the potential to provide greater CV benefit, as suggested by meta‐analysis2 and by review of major clinical trials with CCB/RAS blocker therapies 32…”
Section: Discussionsupporting
confidence: 87%
“…In up to 50% of patients in these trials, SBP remained above 140 mm Hg even when patients received multiple antihypertensive therapies from different drug classes, emphasizing that SBP control is difficult to achieve even if DBP has been normalized. However, the current analysis and previous studies2 suggest that better control rates may be achieved even with low‐dose combination therapy than with higher doses of monotherapy.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…19 Fourth, the overall reductions in systolic blood pressure of 3-5 mm Hg achieved by regular physical exercise as well as by exercise accumulation are relatively small compared with the 9 mm Hg reduction reached with antihypertensive drug therapy. 20 However, medication is currently not considered a treatment option for the prehypertensive patient. 1 In addition, recent research found that each 5 mm Hg decrease in systolic blood pressure reduced mortality from stroke by 14% and from coronary heart disease by 9%, 6 suggesting that the 4 mm Hg decrease in response to three 10 min walking sessions considerably benefits prehypertensive individuals in terms of reducing their cardiovascular risk.…”
mentioning
confidence: 99%